2005
DOI: 10.1128/jcm.43.1.499-501.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a New Commercial Test, GLABRATA RTT, with a Dipstick Test for Rapid Identification of Candida glabrata

Abstract: This study compares the performance of a 3-h dipstick trehalose test with GLABRATA RTT, a new commercially available 20-min test for the rapid identification of Candida glabrata. With the exception of blood agar, GLABRATA RTT gave reliable results with all media tested and was always superior to the dipstick test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
(6 reference statements)
0
8
0
2
Order By: Relevance
“…and resulting modification of antifungal therapy (37). Another major advantage cited by all current studies is the rare incidence of incorrect identification reported when the identification score was within the "acceptable" category (17,20,21,24). Isolates that generated poor-quality spectra and species not present in the reference library received low identification scores and were categorized as "unacceptable identification."…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…and resulting modification of antifungal therapy (37). Another major advantage cited by all current studies is the rare incidence of incorrect identification reported when the identification score was within the "acceptable" category (17,20,21,24). Isolates that generated poor-quality spectra and species not present in the reference library received low identification scores and were categorized as "unacceptable identification."…”
Section: Resultsmentioning
confidence: 97%
“…However, not all C. albicans isolates produce germ tubes, and other Candida species, most notably C. tropicalis and C. dublinensis, can also form similar structures that may be misinterpreted as germ tubes (19). Similarly, a positive rapid assimilation of trehalose (RAT) test can presumptively identify C. glabrata, but several species, including C. tropicalis, can produce false-positive results if the test is performed incorrectly (20). Because of these limitations, rapid tests often must be confirmed using additional methods.…”
Section: Current Methods For the Identification Of Yeasts And Yeast-lmentioning
confidence: 99%
“…This property of C. glabrata was subsequently recognized as a rapid and cost-effective means to identify this pathogen (Land et al 1996;Fenn et al 1999;Lopez et al 2001;Soussi-Abdallaoui et al 2003;Freydiere et al 2003Freydiere et al , 2004Murray et al 2005;Willinger et al 2005;Fraser et al 2012). These rapid diagnostic tests could theoretically impact patient care by affecting therapy selection, especially in cases of candidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Latex agglutination kits are now commercially available and allow a species identification of C. albicans , Candida dubliniensis and C. krusei within minutes (Table 1) [43–45]. C. glabrata can be rapidly identified because of its high amounts of preformed intracellular trehalase enzyme [43,45–48]. Finally, peptide nucleotide analogue probes and fluorescence microscopy can be used [27,29,30].…”
Section: Mycological Diagnosticsmentioning
confidence: 99%